An online model of international clinical mentoring for novice physical therapists. (27th May 2018) - Westervelt, Karen C.; Hing, Wayne; McGovern, MaryClaire; Banks, Lora; Carney, Carolyn; Kunker, Katrina; Magoon, Ashley; Sibold, Jeremy; Crane, Linda
Abstract: Objectives: Clinical mentoring is important for novice clinicians as they are developing advanced critical-thinking skills. Research exploring innovative mentoring strategies to reduce barriers and enhance learning is needed. The purpose of this study was to examine the effects of providing online clinical mentoring to small international groups of novice clinicians treating patients with spinal dysfunction in the outpatient setting. Methods: Eleven novice and four expert clinicians were allocated into small international groups. Four one-hour group video-conference mentoring sessions were held in which each novice clinician presented a case study. Data were collected from pre- and post-participation surveys and post-participation focus groups. Data were evaluated with a mixed-methods phenomenological analysis. Results: Four themes emerged from the novice qualitative data: improved confidence, enhanced critical thinking, appreciation of the structured design and accessibility to peers and mentors. The quantitative data revealed significant improvement in three confidence measures, improvement of 1.48 points on self-selected clinical goals, and 82.0% reported improved clinical decision-making. Two themes emerged from the expert data: value of the model to fill a need within the profession and viability of the model to stand alone or as part of an educational program. All participants rated their experience on average at 8.76/10 and expressed interest in future mentoring programs. Discussion: Online small group international clinical mentoring appears to be an effective strategy to provide clinical mentoring to promote confidence and critical-thinking skills. This research could provide a viable model to increase accessibility to clinical mentors and fill a need within the profession.